2017
DOI: 10.21605/cukurovaummfd.357176
|View full text |Cite
|
Sign up to set email alerts
|

Antakya-Cilvegözü Karayolu Etrafındaki Tarım Arazilerinde ve Bitkilerdeki Ağır Metal Kirliliği

Abstract: ÖzBu çalışmada, Hatay İline bağlı Antakya-Cilvegözü uluslararası karayolu çevresindeki tarım arazilerinin ve bu arazilerde yetişen bitkilerin trafik ve tarımsal faaliyet kaynaklı ağır metal kirliliğini belirlemek, toprak ve bitkideki ağır metal miktarının karayoluna olan uzaklığı ile olası değişimini ortaya koymak amaçlanmıştır. Karayolunun trafik yoğunluğu dikkate alınarak 8 farklı örnekleme noktası belirlenmiştir. Karayolunun belirlenen her bir örnekleme noktasının sağ ve sol tarafından yola 25, 100, 500 m v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 8 publications
0
9
0
2
Order By: Relevance
“…When the change in heavy metal accumulation by years is considered, according to the mean values of 23 soil samples, Cr, Cu, and Pb increased, while Co, Ni, Zn, and Cd decreased. e increase is mostly attributed to motor vehicles and the increase due to agricultural activities are estimated to be limited [9,14] Heavy metal accumulation values in the soil alone do not make sense. Each country sets permissible limit values in line with its own conditions.…”
Section: Heavy Metal Contents Of the Soil Samplesmentioning
confidence: 99%
See 4 more Smart Citations
“…When the change in heavy metal accumulation by years is considered, according to the mean values of 23 soil samples, Cr, Cu, and Pb increased, while Co, Ni, Zn, and Cd decreased. e increase is mostly attributed to motor vehicles and the increase due to agricultural activities are estimated to be limited [9,14] Heavy metal accumulation values in the soil alone do not make sense. Each country sets permissible limit values in line with its own conditions.…”
Section: Heavy Metal Contents Of the Soil Samplesmentioning
confidence: 99%
“…Various studies investigating the heavy metal pollution due to motor vehicles using soil and plant samples, the changes depending on the distance to highway, soil depth, soil structure, and content are considered [1,2,9,[14][15][16]. Particularly, it has been determined that heavy metal content decreases depending on the distance of the highway [9,14,16]. According to Bilge and Çımrın [14], it was observed that Pb, Cd, Ni, Cr, and Cu contents decreased as they were moved away from the highway.…”
Section: E Heavy Metal Contents Of Soil Samples Based On Thementioning
confidence: 99%
See 3 more Smart Citations